2016
DOI: 10.1590/0102-6720201600010002
|View full text |Cite
|
Sign up to set email alerts
|

The Panc 3 Score Predicting Severity of Acute Pancreatitis

Abstract: Background : About 20% of cases of acute pancreatitis progress to a severe form, leading to high mortality rates. Several studies suggested methods to identify patients that will progress more severely. However, most studies present problems when used on daily practice. Objective : To assess the efficacy of the PANC 3 score to predict acute pancreatitis severity and its relation to clinical outcome. Methods : Acute pancreatitis patients were assessed as to sex, age, body mass index (BMI), etiology of pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 27 publications
1
12
0
4
Order By: Relevance
“…This is in agreement with many prior studies that have indicated that both the RAC and the DBC strongly predict length of hospital stay better than OAC without any significant differences between them [9,10,22]. Further, while little work has been done to assess the predictive capacity of BISAP and PANC 3 on LOS, both systems have been shown to have predictive capacity at identifying severe AP as defined by RAC and DBC [4,17,19]; so it logically follows that their predictive capacity at identifying the length of stay should be similar to RAC and DBC. We suggest that BISAP and PANC3, which can be obtained within the initial 24 h of a patient's stay, may be useful to offer the early prediction of length of stay and RAC and DBC can offer further information later in the course of the disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in agreement with many prior studies that have indicated that both the RAC and the DBC strongly predict length of hospital stay better than OAC without any significant differences between them [9,10,22]. Further, while little work has been done to assess the predictive capacity of BISAP and PANC 3 on LOS, both systems have been shown to have predictive capacity at identifying severe AP as defined by RAC and DBC [4,17,19]; so it logically follows that their predictive capacity at identifying the length of stay should be similar to RAC and DBC. We suggest that BISAP and PANC3, which can be obtained within the initial 24 h of a patient's stay, may be useful to offer the early prediction of length of stay and RAC and DBC can offer further information later in the course of the disease.…”
Section: Discussionsupporting
confidence: 90%
“…However, it exhibits low sensitivity for severe pancreatitis [17]. Similarly, while Panc 3 and HAPS have been shown to be accurate at predicting severe AP with high specificities, they also exhibit low sensitivities [18][19][20]. Finally, while SNNAP is simple and effective at predicting readmission within a thirty-day period, it has limited utility outside of this [21].…”
Section: Introductionmentioning
confidence: 99%
“…In study by Beduschi et al in 2016 pleural effusion had sensitivity of 60%, specificity of 91.7%, PPV of 60%, NPV of 91.7%. 17 In a prospective study by Rathnakar et al in 2017 patients with SAP showed abnormal X-ray findings suggestive of pleural effusion in 18 (78.3%). 18,19 As compared to abnormal findings of 9 (15.3%) patients among 59 patients with mild attack (Chi-square test showed p<0.001).…”
Section: Discussionmentioning
confidence: 95%
“…En el grupo de pacientes estudiados, encontramos promedios de edades similares, siendo el sexo masculino el más encontrado en PA severa y mostrando ser estadísticamente signficativo (Tabla 1), este hallazgo coincide con lo publicado por Beduschi et al (23) , en Brasil en el año 2016, donde el sexo se asocia de una manera significativa con PA severa. Con respecto a la edad Jimenez et al (24) en el año 2015 en Perú y Tabla 1.…”
Section: Discussionunclassified